Using Structured Positive and Negative Reinforcement to Change Student Behavior in Educational Settings in order to Achieve Student Academic Success - J. Kelly; B. Pohl (Multidisciplinary Journal for Education, Social and Technological Sciences)
Typically, classroom management approaches for dealing with disruptions and misbehavior from students involve the use of various forms of punishment: removal from the classroom, fines, in-school and out-of- school suspensions, or expulsions (Garret, 2015).  However, traditional classroom management methods have yielded very little positive results. Some would even argue that classroom behaviors are escalating out of control. Using research based approaches; this article’s goal is to help teachers discover student-centered approaches that will positively improve discipline inside the classroom.